Detection of community‐acquired respiratory viruses in allogeneic stem‐cell transplant recipients and controls—A prospective cohort study. Issue 6 (23rd July 2020) - Rachow, Tobias; Lamik, Toni; Kalkreuth, Jana; Kurze, Stephanie; Wagner, Kathleen; Stier, Pia; Hammersen, Friedrich J.; Rüthrich, Maria Madeleine; Winkelmann, Nils; Klink, Anne; Hilgendorf, Inken; Hermann, Beate; et al.
Abstract: Background: Community‐acquired respiratory viruses (CARV) cause upper and lower respiratory tract infections (URTI/LRTI) and may be life‐threatening for recipients of an allogeneic stem cell transplantation (allo‐SCT). Methods: In a prospective study encompassing 4 winter‐seasons, we collected throat gargles (TG) at random time points from allo‐SCT recipients (patients) and controls and followed them up for at least 3 weeks including repetitive sampling and documentation of symptoms. A Multiplex‐PCR system to identify 20 CARV and Mycoplasma pneumoniae was used to detect CARV. Results: One hundred ninety‐four patients with 426 TG and 273 controls with 549 TG were included. There were more patients with a positive test result (25% vs 11% in the controls), and the patients had a higher number of positive TG (70 = 16%) compared to controls (32 = 6%) ( P  < .001). Altogether, 115 viruses were detected. Multiple viruses in one TG (11/48, 34%) and prolonged shedding were only observed in patients (13/48, 27%). Patients had more RSV (18/83, 26%) and adenovirus (15/83, 21%) than controls (both viruses 2/32, 6%). Independent risk factors for the detection of CARV included age >40 years (OR 3.38, 95% CI 1.8‐6.4, P  < .001) and presence of URTI‐symptoms (OR 3.22, 95% CI 1.9‐5.5, P  < .001). No controls developed a LRTI or died whereas 4/48 (8%) patients developed a LRTI (coronavirus in 2, RSV in 1 and influenza A H1N1 in 1 patient). One patient died of CARV (influenza A H1N1). Conclusion: Allo‐SCT‐recipients have more CARV‐infections, exhibit a different epidemiology, have more cases of co‐infection or prolonged shedding and have a higher rate of LRTI and mortality.